Prevalence of obesity and impact of socio-demographic factors on obesity in 15-19 years old adolescents in Vojvodina, Serbia - Petrović, Vesna; Čanković, Sonja (Central European journal of public health, 2023)
OBJECTIVES: The aim of this study was to examine the prevalence of overweight/obesity in 15-19 years old adolescents in the Province of Vojvodina, Serbia, and to evaluate the association between obesity and socio-demographic factors. METHODS: A cross-sectional study was conducted in high schools in the territory of Vojvodina, Serbia. The sample consisted of 986 high-school students (47.4% girls and 52.6% boys). Body height, body weight, and waist circumference were measured. Obesity was defined as a body mass index (BMI)-for-age value > x̅ + 2 SD, and overweight as a BMI-for-age value > x̅ + 1 SD and ≤ x̅ + 2 SD. Waist-to-height ratio (WHtR) of ≥ 0.5 was considered high risk. Socio-demographic data was collected using a questionnaire developed for this study. Univariate and multivariate logistic regression analyses were implemented. RESULTS: The prevalence of overweight and obesity in adolescents was 19.6% and 10.1%, respectively. Boys were more likely to be obese than girls (OR = 1.87; 95% CI: 1.37-2.56). Adolescents living in suburban areas had a greater chance of obesity compared to those living in urban areas (OR = 1.84; 95% CI: 1.15-2.94), as well as those who attended trade schools compared to gymnasium students (OR = 1.92; 95% CI: 1.20-3.07). The lower level of the father's education was a significant predictor of obesity. Predictors of high-risk WHtR were gender, high school type, and the father's education level. CONCLUSIONS: Obesity and abdominal obesity are highly prevalent in adolescents in Vojvodina, more in boys. Gender, community type and the level of the father's education were confirmed as significant factors that influenced both obesity and abdominal obesity. This study could help to customize health promotion policies for adolescents in Vojvodina.
Keywords: obezita dětí a dospívajících; dospělí; Obesity, Abdominal; Female; Overweight; Prevalence; Yugoslavia; Adult; Srbsko; mladý dospělý; ženské pohlaví; průřezové studie; obvod pasu; adolescents; Adolescent; Obesity; lidé; Serbia; Jugoslávie; Waist Circumference; waist circumference; prevalence; Cross-Sectional Studies; obezita; Male; body mass index; Young Adult; index tělesné hmotnosti; nadváha; mužské pohlaví; abdominální obezita; Body Mass Index; obesity; mladiství; prevention; Pediatric Obesity; Humans